2016
DOI: 10.1021/acschemneuro.5b00319
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of [18F]RAGER: A First Generation Small-Molecule PET Radioligand Targeting the Receptor for Advanced Glycation Endproducts

Abstract: The receptor for advanced glycation endproducts (RAGE) is a 35kDa transmembrane receptor that belongs to the immunoglobulin superfamily of cell surface molecules. Its role in Alzheimer’s disease (AD) is complex, but it is thought to mediate influx of circulating amyloid-β into the brain as well as amplify Aβ-induced pathogenic responses. RAGE is therefore of considerable interest as both a diagnostic and a therapeutic target in AD. Herein we report the synthesis and preliminary pre-clinical evaluation of [18F]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(76 citation statements)
references
References 50 publications
5
71
0
Order By: Relevance
“… 18 This binding appeared to be largely dependent on hydrophobic interactions with Pro45, Leu49, Trp51, Pro66, Leu78, and Pro80. 18 …”
Section: Development Of Rage Inhibitors 1 – mentioning
confidence: 95%
See 2 more Smart Citations
“… 18 This binding appeared to be largely dependent on hydrophobic interactions with Pro45, Leu49, Trp51, Pro66, Leu78, and Pro80. 18 …”
Section: Development Of Rage Inhibitors 1 – mentioning
confidence: 95%
“… 18 [ 18 F] 13 was obtained using a trimethylammonium precursor and [ 18 F]fluoride in the presence of Kryptofix-2.2.2 (K2.2.2) in DMF at 130 °C for 30 min. 18 In vitro autoradiography of human brain tissue showed higher uptake of [ 18 F] 13 in the frontal cortex of AD compared with healthy control tissue. However, when studied in vivo, significant nonspecific binding to the white matter was observed, peaking within 3 min post iv injection and followed by virtually complete washout over the duration of the PET scan.…”
Section: Development Of Rage Inhibitors 1 – mentioning
confidence: 99%
See 1 more Smart Citation
“…[15] Similar to the situation in tumor microenvironment, oxidative stress is leveraged to trigger drug release in ROS-responsive drug delivery systems for AD treatment. [20] Based on the aberrant hyperreactive state of microglia and the associated microenvironment changes in the early stage of AD progression, we herein present a polymeric micelle drug delivery system (Ab-PEG-LysB/CUR) with sequential targeting ability to normalize AD microenvironment via microglia modulation. [8c] The hindrance of blood-brain barrier (BBB) and the locusspecific intracerebral drug distribution should also be taken into consideration for AD drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, as described above, RAGE is as an important subject of research [174], and in vitro and in vivo studies have demonstrated the potential of RAGE as a therapeutic target in neurodegeneration [150,151,[175][176][177]. Additional studies will be important to confirm this.…”
Section: Targeting Glycation As a Therapeutic Approach In Hdmentioning
confidence: 86%